2004
DOI: 10.1111/j.1460-2466.2004.tb02636.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Distance Learning: A Comparison Using Meta-Analysis

Abstract: This article uses meta-analysis to summarize the quantitative literature comparing the performance of students in distance education versus traditional classes. The average effect (average r = .048, k = 39, N = 71,731) demonstrates that distance education course students slightly outperformed traditional students on exams and course grades. The average effect was heterogeneous, and the examination of several moderating features (presence or absence of simultaneous interaction, type of channel used in distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(93 citation statements)
references
References 55 publications
5
80
0
8
Order By: Relevance
“…Although not social work specific, meta-analyses comparing distance education and classroom instruction reveal somewhat mixed results with support leaning toward distance education being similar to traditional classroom instruction. Allen et al (2004) and Sitzman, Kraiger, Stewart and Wisher (2006) found no differences in educational effectiveness for distance learners, with effectiveness defined as assessment of student performance (e.g., grades) or acquisition of declarative knowledge. However, Bernard et al (2004) found wide variability and low effect sizes on various outcomes including student achievement, attitude, and retention.…”
Section: Discussionmentioning
confidence: 99%
“…Although not social work specific, meta-analyses comparing distance education and classroom instruction reveal somewhat mixed results with support leaning toward distance education being similar to traditional classroom instruction. Allen et al (2004) and Sitzman, Kraiger, Stewart and Wisher (2006) found no differences in educational effectiveness for distance learners, with effectiveness defined as assessment of student performance (e.g., grades) or acquisition of declarative knowledge. However, Bernard et al (2004) found wide variability and low effect sizes on various outcomes including student achievement, attitude, and retention.…”
Section: Discussionmentioning
confidence: 99%
“…Though many issues existing in FtF courses find a similar underlying set of considerations and applications in online courses, the online learning environment offers its own set of challenges, as well as opportunities. As metaanalyses comparing online and FtF learning established similar levels of cognitive learning and student satisfaction (Allen et al, 2002, Allen et al, 2004, the challenge for online instructors becomes how to best facilitate positive student outcomes. This research furthers that understanding by (1) supporting previous research in FIT (Kluger & DeNisi, 1996) by identifying negative emotional predisposition to instructor feedback as a significant negative predictor of student motivation toward online courses, and; (2) indicating that recognizing high levels of teaching presence in a current online course does not guarantee high student motivation toward online courses more generally.…”
Section: Resultsmentioning
confidence: 99%
“…Such an approach toward designing and facilitating an online course likely intuitively makes sense to instructors, as the course material would seem to reflect MRT's notion of complex information that would warrant a rich medium in order to be effectively sent and received. However, some previous research (Allen et al, 2004) suggests that using as many channels as possible, in attempt to re-create the traditional FtF classroom as closely as possible online, might not increase student satisfaction with the modality. As Feaster (2010) suggests, having multiple channels available can potentially influence an interaction, but ultimately, individuals' preferences, and actual use of the channels, may determine the result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Sitzmann et al (2006) reported that OE teaching is 6% more effective than FTF for teaching declarative knowledge, and Allen et al (2004) reported that OE students slightly outperformed FTF students on exams and course grades.…”
Section: Comparison Of Ftf and Oementioning
confidence: 99%